Penggunaan Sari Umbi Bawang Merah pada Pembibitan Pepaya - Faryska Nur Ichsan; Djoko Purnomo; Linajanti Darsana (Agrosains : Jurnal Penelitian Agronomi, 2013)
People awareness toward nutritious food through the consumption of fruit is rising. Therefore, it needs the increasing of seed availability, either from the planting expansion or cultivation technology development. The productive life of papaya is around 3 years, so the rejuvenate of plant takes relatively quickly. However, the obstacle occurred comes from the adequate life of seed availability and the limitedness of homogeneous seed. Therefore, young seed forced to be used in the field will cause the growth of the plant not in unison. Moreover, it is also not profitable if it is considered from the cultivation of seedlings, since the price of the seed will be cheaper. This research aims to get papaya’s seed which can grow fast and uniformly using growth stimulant substance just like gibberellins that is easy to get and cheap. The experiment studies using concentrations of union juice as the substance to soak the planting material seed of papaya before it is planted. The test of durability and germination speed toward 10 seeds on opaque paper in a petri dish germination medium which the diameter is 11,5 cm. The experiment of seeds growth uses completely randomized design (RAL) in a factor of water treatment, the concentration of union juice is 5, 10, 15, and 20 ml l-1, and 10 ppm gibberellin. Every treatment (experimental unit) consists of 8 seeds planted on the traypot (combination of plastic pots, which each size about: on the surface and high 5,5x5, 5x5,5 cm, pots base 2,5x2,5 cm, an each traypot consists of 32 pots). Thus, there were 8 unit experiments for each traypot, and every single unit of experiments is repeated 3 times. Traypot and petri dish are put beneath the roof in the terrace protected by paranet 65% with 2,5x1,5x2,0 m (length, width, and height) in size. The union juice which is potential is used as the substitute of plant growth regulators gibberellins in papaya seedling. The response of papaya seed toward union juice with 15 ml l-1 concentration is equal to 10 ppm gibberellin, occurred in germination (durability and speed of germination) and the seed growth (the root length, the stem diameter, number of leaves, and biomass weight).